2023
DOI: 10.3390/separations10080448
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification and Characterization of a Novel Rusticyanin from the Psychrotolerant Acidithiobacillus ferrivorans

Abstract: Rusticyanin plays a crucial role in ferrous oxidation of sulfide minerals during bioleaching for industrial metal extraction. Diverse isoforms of rusticyanin have been found, but until now, except for type-A rusticyanin, other isoforms or sources of rusticyanin have been scarcely investigated. Here, a rusticyanin (gene locus 0470) from the psychrophilic Acidithiobacillus ferrivorans was gene-cloned, expressed, purified, and assembled in vitro. All forms of the protein exhibit extreme acid stability, even at pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…The second-order rate constant of the ferrous ion by the oxidation of the iron oxidase in our determination was about 2-3 times faster than those of the reported Chromatium HiPIP, although they were in different solution conditions and reaction directions. Moreover, the kinetic rate of ferrous oxidation by the protein is also obviously faster than that of rusticyanins previously reported [39]. Therefore, our result well supports the view that the iron oxidase plays a role as the initial electron receptor from the ferrous ion in the ferrous biooxidation of the microorganism.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The second-order rate constant of the ferrous ion by the oxidation of the iron oxidase in our determination was about 2-3 times faster than those of the reported Chromatium HiPIP, although they were in different solution conditions and reaction directions. Moreover, the kinetic rate of ferrous oxidation by the protein is also obviously faster than that of rusticyanins previously reported [39]. Therefore, our result well supports the view that the iron oxidase plays a role as the initial electron receptor from the ferrous ion in the ferrous biooxidation of the microorganism.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous study of rusticyanin also exhibited similar shapes and characteristic absorptions [39]. The most obvious difference between the spectra of the oxidized and reduced iron oxidase is in the region range from 1450 to 400 cm −1 , which can be taken as a characteristic fingerprint of conformational change to define the transient states of the protein [39]. A previous study of Clostridial ferredoxin reported that the infrared absorbance peak at 1050 cm −1 , which was quite prominent in native ferredoxin, was absent in apoferredoxin [32].…”
Section: Characterizations Of the Iron Oxidasesupporting
confidence: 60%
See 3 more Smart Citations